THE ROLE OF YOUTH RED CROSS (PMR) IN INSTALLING ATTITUDE SOCIAL CONCERN AND HEALTHY LIFESTYLE PATTERNS OF STUDENTS AT SDN 20 MATARAM - meri ariantini (JOETAL: Journal of Education, Teaching and Learning, 2024)
This research was motivated by the author's attention regarding the role of the Youth Red Cross in instilling attitudes of social awareness and healthy lifestyles in students at SDN 20 Mataram. The objectives of this research are (1) to determine the role of the Youth Red Cross (YRC) in instilling attitudes of social awareness and healthy lifestyles in students at SDN 20 Mataram (2). To find out the obstacles and solutions to the role of the Youth Red Cross (YRC) in instilling attitudes of social awareness and healthy lifestyles in students at SDN 20 Mataram. This type of research uses qualitative descriptive research. The data collection methods used were observation, interviews and documentation. The data analysis method used data reduction model, data presentation, and drawing conclusions. The validity of the data used is the expansion of observations, triangulation and adequacy of references. Based on the results of research conducted by researchers, it can be obtained that the role of YRC (Youth Red Cross) at SDN 20 Mataram is carried out through the form of YRC activities which are divided into two, namely routine and period activities. The routine activities are activities carried out every week, such as material both theoretical and practical, YRC (Youth Red Cross) gymnastics, teaching how to wash hands properly and correctly, and community service on Fridays (clean Fridays). Then there are period activities when there are certain competition events which are held once a year, namely the Jumbara (Jumpa Bhakti Gembira) Beginner Level activities held by PMI Mataram City.